Urgensi Persetujuan Pemilik Data dalam Pengelolaan Data Pribadi oleh Platform Digital - Elvina Putri Maheswari; Sidi Ahyar Wiraguna (CV. ITTC INDONESIA, 2025)
The advancement of information technology has led to an increase in the collection and processing of personal data by various digital platforms. This phenomenon presents new challenges in the protection of privacy rights, particularly regarding the importance of consent as a legal basis for data management. This study aims to analyze the urgency of data subject consent in the management of personal data by digital platforms and to evaluate the effectiveness of its regulation under Law Number 27 of 2022 on Personal Data Protection. The main problem formulation focuses on how consent functions in ensuring legal protection for data owners and how its implementation is carried out in practice. This research applies a normative juridical method through statutory and literature approaches. The results show that although the PDP Law explicitly regulates the principle of consent, there remain implementation gaps in the field, including lack of information transparency, unclear consent mechanisms, and weak supervision. Therefore, reinforcement is needed through derivative regulations, the development of effective control mechanisms, and the improvement of public digital literacy. The conclusion affirms that consent is not merely an administrative formality but a fundamental guarantee of private rights protection. Recommendations are provided for policymakers and digital service providers to establish a trustworthy and law-abiding data governance system.